DiBiCoo: Biogas Markets and Frameworks in Argentina, Ethiopia, Ghana, Indonesia, and South Africa - Rahmatzafran, Avila; Rosslee, Dwight; Rianawati, Elisabeth; Hafiz Loeksmanto, Ichsan; Hilbert, Jorge Antonio; Alemmu, Sinshaw; Mohammed, Mutala; Salie, Yaseen; Bogale, Wondwossen (DiBiCoo, 2022)
In Argentina, the biogas market has gained a solid foothold over the last five years and is massively industrial. However, its growth is slowing down. In 2015, Argentina has developed 100 biogas plants and has grown exponentially until 2020 through the RenovAr Programme. In 2015, INTA and PROBIOMASA have conducted a survey assessing 80 of the 100 plants built nationwide. INTA and PROBIOMASA have found that from the 80 plants surveyed, 76 of the 80 biogas plants developed up until 2015 were installed for environmental purposes, while 11 of the 80 biogas plants surveyed were utilised for energy development, consisting of large bio-digestion plants (1MW-2MW), consisting mostly of covered lagoon and mixed technologies utilising digesters, double membrane reactor, and a co-generation unit i.e. combined heat and power (CHP). It must be noted that at that time biogas was not widely used as a source of energy, rather, it was used for environmental purposes. The relatively slow growth of the biogas market until 2015 is also indicated by the low rate of biogas utilisation for the means of energy security. It is also worth highlighting that the dominating feedstock utilised for biogas in Argentina is industrial waste, followed by organic waste and virgin biomass. To accelerate the growth of the biogas market, Argentina has been implementing governmentled programs. The most notable program is the series of RenovAr programs i.e. round 1, round 1.5, and round 2) that was started from 2016 and continues until today with RenovAr 3 being implemented in August 2019. According to the World Bank IFC, RenovAR has succeeded in reaching 2.4 GW capacity of combined renewable energy alternatives in the end of 2016 and 4.4 GW of renewable energy projects in August 2017. The tenders foresee a minimum of 0.5 MW and a maximum of 10 MW of electricity capacity from each biogas project to achieve the overall goal. All in all, this program and national goal shows that biogas is seen as an important renewable energy alternative in Argentina. It must also be noted that each country included in this report elaborates on a minimum of four variables of the PESTLE’s framework depending on the degree of its relevancy and influence it has for the biogas sector.